Answer:
[tex]-4(a + b = 6)[/tex]
Step-by-step explanation:
Given
[tex]a + b = 6[/tex]
[tex]4a + 2b = 19[/tex]
Required
Eliminate a
Multiply the first equation by -4
[tex]-4(a + b = 6)[/tex]
Add to the second equation
[tex]-4(a + b = 6) + (4a + 2b = 19)[/tex]
Solve brackets
[tex](-4a -4b = -24) + (4a + 2b = 19)[/tex]
Open bracket
[tex]-4a + 4a -4b + 2b = -24 + 19[/tex]
[tex]-4b + 2b = -24 + 19[/tex]
At this point, a has been eliminated;
From the list of given options, the option that answers the question is [tex]-4(a + b = 6)[/tex]